(untitled) (Swiss Medical Weekly, 2014)
The use of rivaroxaban in fixed dosing regimens without need for routine coagulation monitoring may lead to the misconception that there is a minimal risk of drug-drug interactions. We describe the case of a patient infected with human immunodeficiency virus (HIV) on salvage therapy who developed gastrointestinal bleeding while receiving the standard dose of rivaroxaban for the prevention of venous thromboembolism after surgery. This case clearly sends a warning that protease inhibitors should not be co-administered with rivaroxaban. Furthermore, it highlights the importance of clinicians’ caution about potential drug-drug interactions. Key words: drug-drug interaction; gastrointestinal bleeding; rivaroxaban; protease inhibitor